Effects of the termination of LC30 imidacloprid stress on the multigeneration adaptive strategies of Aphis glycines population - Zhang, Aonan; Dou, Nan; Qu, Zhongcheng; Guo, Yongxia; Zhou, WenJing; Wu, Dongxue; Lin, Zhiying; Feng, Min; Cui, Hengjia; Han, Lanlan (Frontiers in Physiology, 2023)
Aphis glycines Matsumura (Hemiptera: Aphididae) is a major soybean pest that often poses a serious threat to soybean production. Imidacloprid is one of the commonly used insecticides to control the soybean aphid. To investigate the effect of termination of imidacloprid stress on the adaptive strategies of soybean aphid populations, we studied the growth, development, and related metabolism changes when the stress was terminated after 24 generations of imidacloprid stress on A. glycines. The results show that the A. glycines population accelerated its recovery and expanded its population size across generations. The longevity of the adults of the recovering population in the F12, F18, and F24 generations, respectively, was 1.11, 1.15, and 1.11 times longer than the control, while the fecundity was 10.38%, 11.74%, and 11.61% higher than that of the control. The net reproductive rate (R0) of the recovering population was always significantly higher than that of the control in the F1 to F24 generations. In addition, metabolisms related to the regulation of cell proliferation and oocyte meiosis were significantly upregulated in the recovering population. Even when the imidacloprid pressure disappeared, intergenerational stimuli still affected the adaptive strategies of soybean aphid populations. This effect was manifested as inhibiting the growth and development of the soybean aphid in the early generations and improving the fecundity of the soybean aphid in the later generations. Adaptive soybean aphid populations would surge in the absence of imidacloprid pressure. This study provides an important reference for exploring the adaptability of the A. glycines population under termination of stress from low lethal concentrations of imidacloprid across generations. It also provides important data for monitoring the population dynamics of A. glycines in the field and analyzing the degree of pharmacodynamic stress.